The role of religiosity in strengthening resilience, work involvement, and worker performance in Jombang Regency, East Java Indonesia - Firman, Firman; Agus Prianto; Mindaudah, Mindaudah (Technium Social Sciences Journal, 2023)
Strengthening the performance of workers is one of the main issues in efforts to increase work productivity. Various previous studies have identified various factors that affect the performance of workers. Work experience, work commitment, work motivation, job satisfaction, and work compensation are factors that have proven to have a significant effect on the performance of workers. Based on previous studies, few researchers have examined the role of individual religiosity in strengthening worker performance. This study aims to examine the role of individual religiosity in strengthening work involvement, resilience, and performance of workers in Jombang Regency. This research was conducted using a quantitative descriptive research approach, which examines religiosity as the main exogenous variable. While resilience and work involvement as mediating variables, and performance as endogenous variables. Descriptive analysis, path analysis, and univariate analysis were used to answer various research questions. This study reveals that religiosity is the main variable that has a direct effect on resilience, job involvement, and employee performance. Resilience and work involvement then affect the performance of workers. In other words, religiosity plays an important role as the main variable that triggers the performance of workers. Based on the findings in this study, it is suggested that strengthening religiosity can be done early, when prospective workers are studying, and when workers are first accepted into the workplace. It is suggested to other researchers to identify various variables related to the religiosity and performance of workers.